Biopsychosocial factors associated with prurigo nodularis in endogenous eczema - Choon Chiat Oh; Huihua Li; Wellington Lee; Hong Liang Tey (Wolters Kluwer Medknow Publications, 2015)
Background: Prurigo nodularis is a dermatological manifestation secondary to chronic scratching or picking on focal areas of the skin. Its pathogenesis remains poorly understood, and limited data has indicated its association with psychological factors. Aim: To determine the biological, psychological and social factors associated with the occurrence of prurigo nodularis in patients with underlying endogenous eczema. Methods: A prospective case-control questionnaire -based study on patients with endogenous eczema, with and without prurigo nodules, was performed. The Impact of Skin Disease on Daily Life questionnaire was used to assess dimensions of physical functioning, including extent and severity of skin disease, itch, pain, fatigue and scratching, as well as dimensions of psychological and social functioning, including mood, illness cognition, disease-related impact, stigmatization and social support. Results: Thirty-six cases and 47 controls were recruited. Patients with endogenous eczema and prurigo nodules indicated a higher itch score on the visual analog scale over the previous 4 weeks compared to those without prurigo nodules (p=0.0292). There were no significant differences between the 2 groups in the scores reflecting the other parameters of physical, psychological and social functioning. Conclusion: In patients with endogenous eczema, those with prurigo nodules experience a greater itch intensity compared to those without prurigo nodules. There were no other physical, psychological and social factors that were found to be associated with the occurrence of prurigo nodules in endogenous eczema.